1994
DOI: 10.1530/jrf.0.1000447
|View full text |Cite
|
Sign up to set email alerts
|

Chick production by in vitro fertilization of the fowl ovum

Abstract: The aim of this study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In addition, the fimbriae of oviduct should be closed by suture line after the ova located at the anterior magnum, so as to avoid retrograde expulsion into the abdominal cavity. This study also showed that the fertilization rate of IVF was 18% after oocytes ovulated spontaneously, compared with the previous rates of 58% (Tanaka et al. 1994) and 15% (Olszan′ska et al.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…In addition, the fimbriae of oviduct should be closed by suture line after the ova located at the anterior magnum, so as to avoid retrograde expulsion into the abdominal cavity. This study also showed that the fertilization rate of IVF was 18% after oocytes ovulated spontaneously, compared with the previous rates of 58% (Tanaka et al. 1994) and 15% (Olszan′ska et al.…”
Section: Discussionsupporting
confidence: 47%
“…The modified Ringer’s solution consisted of 145 m m NaCl, 2.68 m m KCl, 2.68 m m CaCl 2 , 0.24 m m NaHCO 3 , 1 g/l streptomycin sulphate and 5000 IU/l penicillin (Tanaka et al. 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible to fertilize eggs through AI with frozen samples. The difficulty of using techniques such as intramagnal fertilization [5] and IVF [21,33] urges for the development of cryopreservation techniques allowing a more efficient sperm conservation.…”
Section: Individual Cryopreservation Of Three Avian Speciesmentioning
confidence: 99%
“…Furthermore, Nakanishi et al [11] demonstrated the fertility competency of multiple-ovulated eggs in the chicken after IVF. Tanaka et al [12] produced viable chicks by implanting in vitro-fertilized ova into the oviduct of recipient hens followed by incubation of the eggs. Recently, Olszańska et al [13] investigated development of quail embryos after IVF using in vitroovulated oocytes with a special emphasis on the link between the steps of ovulation and fertilization and with the early cleavage stages under in vitro conditions.…”
Section: Introductionmentioning
confidence: 99%